Capillary Polypropylene Membranes for Membrane Distillation - Marek Gryta (Fibers, 2018)
Only nonwetted porous membranes can be used in membrane distillation. The possibility of application in this process the capillary polypropylene membranes manufactured by thermally-induced phase separation was studied. The performance of a few types of membranes available commercially was presented. The resistance of the membranes to wetting was tested in the continuous process of water desalination. These studies were carried out for 1000 h without module cleaning. The presence of scaling layer on the membranes surface was confirmed by Scanning Electron Microscope observations. Both the permeate flux and distillate conductivity were almost not varied after the studied period of time, what indicates that the used membranes maintained their nonwettability, and the negative influence of scaling was limited. The role of surface porosity on the pore wetting and influence of membrane wettability on the quality of the distillate obtained were discussed.